Decomposing effective radiative forcing due to aerosol cloud interactions by global cloud regimes - Langton, T; Stier, P; Watson-Parris, D; Mulcahy, JP (American Geophysical Union, 2021)
Quantifying effective radiative forcing due to aerosol-cloud interactions (EERFACI) remains a largely uncertain process, and the magnitude remains unconstrained in general circulation models. Previous studies focus on the magnitude of ERFACI arising from all cloud types, or examine it in the framework of dynamical regimes. Aerosol forcing due to aerosol-cloud interactions in the HadGEM3-GA7.1 global climate model is decomposed into several global observational cloud regimes. Regimes are assigned to model gridboxes and forcing due to aerosol-cloud interactions is calculated on a regime-by-regime basis with a 20-year averaging period. Patterns of regime occurrence are in good agreement with satellite observations. ERFACI is then further decomposed into three terms, representing radiative changes within a given regime, transitions between different cloud regimes, and nonlinear effects. The total global mean ERFACI is urn:x-wiley:00948276:media:grl62928:grl62928-math-0003 Wm−2. When decomposed, simulated ERFACI is greatest in the thick stratocumulus regime (−0.51 Wm−2).